Adoption of Water Conservation Practices in Hospitality Establishments in Nakuru County, Kenya - Nthiga, R. W. (Africa Environmental Review Journal, 2022)
Water conservation emerged in response to concerns on environmental degradation. In addition to environmental reasons, hospitality establishments have adopted water conservation practices for economic and social reasons. The purpose of this paper was to examine the adoption of water conservation practices in selected hospitality establishments in Nakuru County, Kenya. The study employed a cross-sectional descriptive research design. The respondents comprised of 120 managers from 15 selected four-star rated hospitality establishments. Census sampling was used to select all four-star hospitality establishments while purposive sampling was used to identify the managers who participated in the study. Data collection instruments comprised of questionnaires for departmental managers, interviews schedules for operations managers and observational checklists to corroborate the data. Reliability of instruments was tested using Cronbach‘s Alpha resulting to a value of 0.766. The study employed descriptive statistics, independent sample t-test and factor analysis in analyzing the data. Repair of leakages was found to be most adopted water conservation practice. Factor analysis results showed that water conservation practices can be measured using three components such as installation practices, maintenance practices and substitution practices.